2001
DOI: 10.1080/09645290110056994
|View full text |Cite
|
Sign up to set email alerts
|

Education and Women's Labour Market Outcomes in India

Abstract: In this paper, we pose the question: to what extent is education responsible for the differential labour market outcomes of women and men in urban India? In particular, we investigate the extent to which education contributes to women's observed lower labour force participation and earnings than men, and whether any contribution of education to the gender wage differential is explained by men and women's differential educational endowments or by labour market discrimination. Our findings suggest that women do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 23 publications
14
86
0
Order By: Relevance
“…Despite best attempts and significant rises in enrolment in most developing countries, recent findings suggest that the target is unlikely to be met 1 . While access to primary schooling has improved substantially, high dropout rates are still a critical problem 2 Studies specific to India have also shown similar results (Kingdon, 1998;Duraisamy, 2002; and Kingdon and Unni, 2001). On the other handsome other studies show that while the actual rate of return to primary schooling is high, parents believe that the first few years of schooling have lower returns than in the later years Duflo, 2005 and2011).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Despite best attempts and significant rises in enrolment in most developing countries, recent findings suggest that the target is unlikely to be met 1 . While access to primary schooling has improved substantially, high dropout rates are still a critical problem 2 Studies specific to India have also shown similar results (Kingdon, 1998;Duraisamy, 2002; and Kingdon and Unni, 2001). On the other handsome other studies show that while the actual rate of return to primary schooling is high, parents believe that the first few years of schooling have lower returns than in the later years Duflo, 2005 and2011).…”
Section: Introductionsupporting
confidence: 59%
“…However, insofar as our results on access to secondary schooling survive all specifications, we do not forsake the fixed effects estimation models. 16 Lavy (1996) used distance to public telephone and post office as instruments for distance to middle school.…”
Section: Instrumental Variablesmentioning
confidence: 99%
“…Given that being a woman reduces the probability of attaining primary education by 6 percentage points and being SC/ST reduces it by 18 percentage points, this is considered as an important magnitude 19 . Columns (7)- (9) show results for the probit with endogenous regressors 20 . The coefficients reported are the average marginal effects.…”
Section: The Effect Of Female Legislators On Educationmentioning
confidence: 99%
“…Results for this specification are very similar to the 2SLS results, so 19 These coefficients are not reported in Table 4, but are available from the author on request. 20 Using ivprobit in Stata.…”
Section: The Effect Of Female Legislators On Educationmentioning
confidence: 99%
“…Evidence also suggests that a farm-household's total income depends upon the highest education level reached by a household member rather than by the mean educational level of the household or by the educational level of the household head (Foster and Rosensweig, 1996). To add to this litany, education also raises the wages of both men and women (Kingdon and Unni, 2001 while in the latter situation, he/she is illiterate (Basu and Foster, 1998;Basu, Narayan and Ravallion, 2002).…”
Section: Introductionmentioning
confidence: 99%